High-throughput RNAi screening to dissect cellular pathways: a how-to guide - Falschlehner, Christina; Steinbrink, Sandra; Erdmann, Gerrit; Boutros, Michael (Biotechnology journal, 2010)
RNA interference (RNAi) has become a powerful tool to dissect cellular pathways and characterize gene functions. The availability of genome-wide RNAi libraries for various model organisms and mammalian cells has enabled high-throughput RNAi screenings. These RNAi screens successfully identified key components that had previously been missed in classical forward genetic screening approaches and allowed the assessment of combined loss-of-function phenotypes. Crucially, the quality of RNAi screening results depends on quantitative assays and the choice of the right biological context. In this review, we provide an overview on the design and application of high-throughput RNAi screens as well as data analysis and candidate validation strategies.
Gesehen am 31.07.2023